Amino‐Substituted 2, 2′‐Bipyridine Ligands as Fluorescent Indicators for ZnII and Applications for Fluorescence Imaging of Prostate Cells. Issue 54 (5th September 2018) - Turnbull, William L.; Luyt, Leonard G.
Abstract: Zn II concentrations in malignant prostate tissues are much lower than in benign or healthy, suggesting that Zn II levels are a potential biomarker for prostate cancer (PCa). Five 2, 2′‐bipyridine ligands were synthesized containing amino substituents with varying electron‐donating ability for investigation as fluorescent Zn II indicators. The excited state characteristics of the ligands were explored by UV/Vis and fluorescence spectroscopy. 3, 3′‐Diamino‐2, 2′‐bipyridine (1 ) was previously shown to be weakly fluorescent as a result of π→π* transitions. The other four ligands have properties consistent with an n→π* intraligand charge transfer excited state. Strongly donating amino and aminophenyl (2 and4 ) substituents gave low quantum yields, while weaker donating benzimidazole substituents (6 and7 ) gave high quantum yields. Absorption and fluorescence wavelengths underwent bathochromic shifts upon Zn II binding in a majority of cases. Quantum yields drastically increased upon Zn II binding for1 and2, but decreased for4, 6, and7 . Compounds 6 and7 were incubated with PC‐3, DU 145 and BPH‐1 cells to determine their Zn II sensing abilities in a biological system. Weak fluorescence was observed in BPH‐1 cells and subsequent incubation with Zn II caused fluorescence intensity to increase. No fluorescence was observed in PCa cell lines. Further investigation of these ligands may allow for quantitative determination of Zn II concentrations in ex vivo tissue samples. Abstract : Shedding light on zinc : Fluorescent detection of Zn II in biological tissues has implications for the diagnosis of disease. Five amino‐substituted bipyridine ligands were synthesized as fluorescent indicators that change their fluorescence emission properties in the presence of Zn II . Two of these bipyridine ligands were used to differentiate malignant and benign prostate cells through Zn II ‐mediated fluorescence by confocal microscopy.